Readiness of fashion education and training institutions management in facing the industrial revolution 4.0 and society 5.0 - Miftahul Annisah Nurfitria; Widihastuti Widihastuti; Nur Kholifah; Sayidatul Maslahah (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This study aims to determine how the management of education and fashion training institutions is prepared to face the industrial revolution 4.0 and society 5.0. This research is a case study research by examining field conditions. The data collection method is triangulation with observation, interviews, and documentation. The data of this study were obtained from the head of the institution, instructors, and course students. Technique triangulation and source triangulation were carried out to check the validity of the data. The research was conducted at the Yogyakarta Career Busana course and training institute. The research results based on the principles of POAC (planning, organizing, actuating, controlling) include the condition of the institution's management such as the institution's program curriculum, institutional management, strategy, program implementation, and control strategies and techniques in management. The results show that a strategy is needed to increase the readiness of educational institutions and fashion training for industrial revolution 4.0 and society 5.0. The development strategy can be seen from several aspects of the management function, namely planning, organizing, activating, and controlling. Institutions that have good readiness for the industrial revolution 4.0 and society 5.0 have aspects of management functions that are by the development, needs, and conditions of the industrial revolution 4.0 and society 5.0.